2019
DOI: 10.3390/ani9110969
|View full text |Cite
|
Sign up to set email alerts
|

3Rs-Related and Objective Indicators to Help Assess the Culture of Care

Abstract: Simple Summary‘Culture of Care’ within animal research and testing refers to a commitment to improve animal welfare, the quality of the science, staff morale, and openness with the public. An effective Culture of Care should also promote the replacement of animal experiments with humane alternatives, reductions in animal numbers and suffering, and better welfare through the refinement of procedures, housing, husbandry and care (collectively known as the 3Rs). The Culture of Care is recognized as the foundation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 2 publications
0
18
0
1
Order By: Relevance
“…We would like to highlight that there are objective indicators of a Culture of Care that can be reviewed, assessed and used to drive improvements in establishments. 2,6 Readers are strongly encouraged to familiarize themselves with these indicators. A list of indicators that relate to the AWB itself can be found in Robinson et al; 2 selected examples can be found in Table 1.…”
Section: Results and Reflections From The Workhopmentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to highlight that there are objective indicators of a Culture of Care that can be reviewed, assessed and used to drive improvements in establishments. 2,6 Readers are strongly encouraged to familiarize themselves with these indicators. A list of indicators that relate to the AWB itself can be found in Robinson et al; 2 selected examples can be found in Table 1.…”
Section: Results and Reflections From The Workhopmentioning
confidence: 99%
“…These good practice indicators can help bring some structure to building a Culture of Care and would be a good basis to start discussions within your establishment. 2,6 We reiterate the importance for providing better opportunities for open and safe discussions on feelings and emotions among the professionals working in the field of laboratory animal research. More attention should be given for recognizing and rewarding positive behaviors and actions of staff.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of the study are -to the authors' knowledge -not published. Recently, Hawkins and Bertelsen (2019) provided 3Rs indicators to help assess the culture of care at the level of a facility. Those separate initiatives can pave the way to further actions and can be used as a baseline for future comparisons when the next statistics are released.…”
Section: Authorization Of Animal Experimentsmentioning
confidence: 99%
“…These summaries are published in the Similar investigations were performed elsewhere. For example, Taylor (2014) Hawkins and Bertelsen (2019) provided 3Rs indicators to help assess the culture of care at the level of a facility. Those separate initiatives can pave the way to further actions and can be used as a baseline for future comparisons when the next statistics are released.…”
Section: Authorization Of Animal Experimentsmentioning
confidence: 99%